2017
DOI: 10.1371/journal.pntd.0005573
|View full text |Cite
|
Sign up to set email alerts
|

Associations between selective attention and soil-transmitted helminth infections, socioeconomic status, and physical fitness in disadvantaged children in Port Elizabeth, South Africa: An observational study

Abstract: BackgroundSocioeconomically deprived children are at increased risk of ill-health associated with sedentary behavior, malnutrition, and helminth infection. The resulting reduced physical fitness, growth retardation, and impaired cognitive abilities may impede children’s capacity to pay attention. The present study examines how socioeconomic status (SES), parasitic worm infections, stunting, food insecurity, and physical fitness are associated with selective attention and academic achievement in school-aged chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 56 publications
3
37
2
2
Order By: Relevance
“…Compared with our study we found that incidence rate for taeniasis and cysticercosis is higher among young people and men that may be more exposed to risk factors as being around infected pigs, eating outside, and low socio-economic conditions as it is previously mentioned [2,44]. …”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Compared with our study we found that incidence rate for taeniasis and cysticercosis is higher among young people and men that may be more exposed to risk factors as being around infected pigs, eating outside, and low socio-economic conditions as it is previously mentioned [2,44]. …”
Section: Discussioncontrasting
confidence: 65%
“…Health education, adequate sanitary habits and wastewater disposal are critical strategies to mitigate the impact of the disease [5,6,18] and reduce economic burden related to losses in meat industry, medical costs and productivity of people affected, especially in countries with social and environmental risk factors such as extreme poverty [2,5,6,9,10,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Chronic morbidity is confounded by polyparasitic infections, nutritional deficiencies, and numerous other factors, such as socioeconomic status and food scarcity, which were unable to be accounted for within the constraints of this study. [3][4][5]45,46 Those children residing at high altitude exhibited higher aerobic capacities than those residing at low altitude. In the former, S. mansoni infection did not have a negative effect on aerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The developed intervention toolkit was pilot-tested among fourth graders in disadvantaged primary schools in Port Elizabeth, South Africa. The preliminary findings suggest that (i) the prevalence of parasitic worm infection was high in several schools [25]; (ii) children infected with soil-transmitted helminths had lower maximal oxygen uptake compared to their non-infected peers [26]; (iii) helminth infections and low physical fitness were significant predictors of low selective attention and poor academic achievement [27]; (iv) increased levels of physical activity were associated with a higher health-related quality of life (HRQoL) [28]; (v) increased physical activity levels were associated with lower risks of obesity and hypertension, but increased risk for soil-transmitted helminth infections [29]; and (vi) the DASH physical activity component resulted in small but significant decreases in the body mass index (BMI) of the children [30] and had a positive impact on academic performance within one year [31]. The intervention teaching material used in the DASH study was further elaborated and adapted and then pilot-tested among schoolchildren in grades 4-7 from two disadvantaged primary schools in Port Elizabeth.…”
Section: Introductionmentioning
confidence: 91%